The effect of using the style approach to leadership in developing innovative thinking - exploratory research on the effectiveness of leadership according to the style approach in the General Karbala Cement Company) - علي عبد الحسين جبر الجشعمي, (Iraqi Journal for Administrative Sciences, 2025)
The leadershipofimportantissuesthat gainedthe attention of manyresearchersin the specialty ofmanagement,because of itsfutureimpactinthelivesoforganizations. Theaimoftheresearchwasto see how muchimpacttheApproachmethodof leadership inthedevelopmentofinnovative thinkingamongworkersinKarbalaCementPlant. Theresearch sampleconsistedof(35) members of themanagers and staff. The researcher usedthequestionnaireformas a toolto gather information thatconsisted of(40) is. Researcherconcludedthatleadership practicesaccording totheentranceofstyle, especiallyinterestledtothedevelopmentofworkersthe ability to developideasthatleadtoinnovative waysand meansjobsimprovementofthequalityofproductsKarbalaCementPlant. The researchrecommendedtheneedtoworkto pay attentiontoindividualswithinnovativeideasby strengtheningtheirregulatoryroles, aswellastheirsupportfinancially and morallydeveloped a systemofincentivesencouragesinnovation anddevelops.